The assembly-disassembly-organization-reassembly mechanism for 3D-2D-3D transformation of germanosilicate IWW zeolite - Chlubná-Eliášová, Pavla; Tian, Yuyang; Pinar, Ana B; Kubů, Martin; Čejka, Jiří; Morris, Russell E (Angewandte Chemie (International ed. in English), 2014)
Hydrolysis of germanosilicate zeolites with the IWW structure shows two different outcomes depending on the composition of the starting materials. Ge-rich IWW (Si/Ge=3.1) is disassembled into a layered material (IPC-5P), which can be reassembled into an almost pure silica IWW on treatment with diethoxydimethylsilane. Ge-poor IWW (Si/Ge=6.4) is not completely disassembled on hydrolysis, but retains some 3D connectivity. This structure can be reassembled into IWW by incorporation of Al to fill the defects left when the Ge is removed.
Keywords: germanosilicate; ADOR; IWW; zeolites; solid-state transformation